Bioareactor-on-a chip: application to Baker's yeast fermentation - Soares, Filomena (2000)
This paper presents a miniaturized bioreactor (bioreactor-on-a-chip) applied to baker's yeast fermentation. The bioreactor-on-a-chip is fabricated using a silicon and glass wafers applying micromachining technology (wet-etching techniques) in order to create microchannels, mixerchannels, microvalves. The miniaturization and integration allows smaller volumes to be used, which can be often rather challenging from the analytical point of view. Also, optical detection by absorption, electrochemical detection using microelectrodes and membranes are used. Moreover, electroanalytical techniques used in bioelectrochemistry (e.g. microdialysis, capillary electrophoresis and HPLC) are employed.Experimental results obtained from a macro laboratory set-up with a five-liter fermenter and on-line measurement of temperature, pH, dissolved oxygen and ethanol, and exhausted gases analyses are available. Biomass and glucose concentrations are estimated on-line by observation algorithms and confirmed by off-line measurements. An ethanol set-point control is implemented.